Subjectve Rights, Freedoms and Legitimate Interests of Convicted Persons to Imprisonment - L. B. Smirnov (Теоретическая и прикладная юриспруденция)
The article deals with the theoretical and law enforcement aspects of the subjective rights, freedoms and legitimate interests of convicts serving sentences in prison. The problem of the rights, freedoms and legitimate interests of convicts serving deprivation of liberty remains relevant and needs serious consideration, as it is an integral part of the problem of protection of human rights and freedoms of the individual and the citizen as a whole. Protection of the rights, freedoms and legitimate interests of convicts is an important area of work of lawyers in the conditions of the rule of law.